2022
DOI: 10.1039/d2qi00845a
|View full text |Cite
|
Sign up to set email alerts
|

Tandem ZnCo-porphyrin metal–organic frameworks for enhanced photoreduction of CO2

Abstract: A bimetallic ZnCo-porphyrin metal-organic framework (ZnCo-BMOF) nanosheet was developed for efficient photoreduction of CO2 to CO. The ZnCo-BMOF nanosheet comprises of photosensitizers (Zn porphyrin) and catalysts (Co porphyrin) providing a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…DFT calculations revealed that cobalt sites are favorable for receiving electrons from Zn porphyrin. [ 143 ]…”
Section: D Materials Based On Ferromagnetic Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT calculations revealed that cobalt sites are favorable for receiving electrons from Zn porphyrin. [ 143 ]…”
Section: D Materials Based On Ferromagnetic Elementsmentioning
confidence: 99%
“…DFT calculations revealed that cobalt sites are favorable for receiving electrons from Zn porphyrin. [143] Therefore, the utilization of nickel-based or cobalt-based 2D materials in photocatalytic applications is not only attributed to the beneficial conductive properties and to the strong binding energy with H 2 and CO 2 , but also to the synergy with other metals; in this way, the overall photocatalytic performance of the materials can be enhanced. At the same time, the low dimensionality offers a shorter charge transport path and boosts light harvesting ability.…”
Section: Photocatalysismentioning
confidence: 99%
“…For example, photocatalytic CO 2 reduction can produce various fuels such as CO, formic acid, and hydrocarbons [ 103 ]. In recent years, MOFs have been widely studied for photocatalytic CO 2 reduction due to their adjustable composition and structure, easy integration with other functional substances, and large surface area [ 136 , 137 , 138 , 139 ].…”
Section: Application Of Porphyrin-based Mofs In Photocatalysismentioning
confidence: 99%
“…The porous architecture of this family of 2D-MOFs driven by the reticular chemistry of the metal centers and the organic linkers creates conducting channels and the π–π electron conjugation in the porphyrin ligands brings forth excellent electronic conductivity in these 2D materials. The additional structural features of the 2D-MOFs include a larger surface area, conducive diffusion of gases in the framework, and mechanical stability. The metalloporphyrin MOFs have been reported as active electrocatalysts and photocatalysts for hydrogen evolution reaction (HER) and CO 2 RR (CO 2 reduction reaction), C–H activation, and nitrous oxide decomposition. The extraordinary performance of metalloporphyrin MOFs in CO 2 RR, a multistep CO 2 reduction to CO and CH 4 as end products, prompted their application into electrocatalysts for nitrogen reduction reaction, which is a six-electron-reduction process.…”
Section: Introductionmentioning
confidence: 99%